A high energy storage potassium bismuth titanate-based relaxor ferroelectric ceramic material with excellent environmental stability and a preparation method thereof

By introducing Ca0.5Sr0.5HfO3 doping into bismuth potassium titanate ceramics, the ion polarization effect is enhanced, and the problems of low breakdown field strength and low energy storage efficiency of bismuth potassium titanate ceramics are solved, and high energy storage density and High efficiency bismuth potassium titanate-based relaxation ferroelectric ceramic material has excellent environmental stability and improved performance.

CN118388236BActive Publication Date: 2024-12-13UNIV OF SCI & TECH BEIJING
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410642607.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-05-23
Publication Date
2024-12-13
Estimated Expiration
2044-05-23

AI Technical Summary

Technical Problem

The low breakdown field strength, low energy storage density and low energy storage efficiency of bismuth potassium titanate ceramic materials limit their application potential in the field of dielectric energy storage.

Method used

By introducing Ca0.5Sr0.5HfO3 doping into the bismuth potassium titanate matrix, the (1-x)Bi0.5K0.5TiO3-xCa0.5Sr0.5HfO3 solid solution was synthesized by solid phase method to enhance the polarization between ions and reduce the residual Polarization and polarization lag improve the breakdown field strength, thereby improving energy storage density and energy storage efficiency.

Benefits of technology

The bismuth potassium titanate-based relaxed ferroelectric ceramic material has achieved high energy storage density, high energy storage efficiency and excellent environmental stability. The breakdown field strength reaches 670 kV/cm, the energy storage density is 14.4 J/cm3, and the energy storage is The efficiency was 88.0%, and showed good stability under different test conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118388236B_ABST
    Figure CN118388236B_ABST
Patent Text Reader

Abstract

The present invention relates to a high energy storage potassium bismuth titanate-based relaxor ferroelectric ceramic material with excellent environmental stability and a preparation method thereof, belonging to the field of dielectric energy storage ceramic materials. The chemical formula of the material is: (1-x)Bi 0.5 K 0.5 TiO3‑xCa 0.5 Sr 0.5 HfO3, where x is Ca 0.5 Sr 0.5 The doping coefficient of HfO3 is x=0.0001~0.4, preferably x=0.06-0.30. When x=0.24, the breakdown field strength of the ceramic material is 670 kV / cm, which is higher than most bismuth potassium titanate-based energy storage ceramics. Its energy storage density is 14.4 J / cm 3 , the energy storage efficiency is 88.0%. In addition, the ceramic also exhibits excellent environmental stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of dielectric energy storage ceramic materials, and specifically relates to a high-energy storage potassium bismuth titanate-based relaxor ferroelectric ceramic material with excellent environmental stability and a preparation method thereof. Background Art

[0002] Ferroelectric materials have the ability to store electrostatic energy due to their spontaneous polarization characteristics, and they play an increasingly important role in the field of energy storage. Lead-based ferroelectric ceramics have the advantages of high field strength resistance and have great advantages in energy storage density and its application, but the use of large amounts of lead elements will seriously harm the environment and human health, and the development of lead-free ceramic capacitors has become an inevitable trend. Lead-free energy storage ceramics often have the advantages of high power density, ultra-fast charging and discharging speed, stable matrix and strong environmental adaptability, but their low energy storage density and energy storage efficiency seriously limit the development of devices towards high-end, miniaturization, intelligence and integration.

[0003] Among lead-free energy storage ceramics, potassium bismuth titanate systems have attracted attention in the field of dielectric energy storage due to their high spontaneous polarization strength. However, their high residual polarization strength and low breakdown field strength result in low energy storage density and efficiency, which restricts the possibility of their application. To address this, at this stage, potassium bismuth titanate-based solid solutions are mainly synthesized by doping with other chemical components, thereby reducing the residual polarization strength, reducing polarization hysteresis, and increasing the breakdown field strength while retaining their high polarization strength, thereby increasing their energy storage density and efficiency, so that they can better meet the needs of practical applications. Summary of the invention

[0004] The technical problem to be solved by the present invention is that potassium bismuth titanate ceramics have low breakdown field strength, low energy storage density and low energy storage efficiency. Therefore, a potassium bismuth titanate-based relaxor ferroelectric ceramic material having high energy storage density, high energy storage efficiency and excellent environmental stability and a preparation method thereof are provided.

[0005] In order to solve the above technical problems, the present invention provides the following technical solutions:

[0006] A high energy storage potassium bismuth titanate-based relaxor ferroelectric ceramic material with excellent environmental stability, the chemical formula of the material is: (1-x)Bi 0.5 K 0.5 TiO3-xCa 0.5 Sr 0.5 HfO3, where x is Ca 0.5 Sr 0.5 The doping coefficient of HfO3 is x=0.0001~0.4, preferably x=0.06-0.30, and most preferably x = 0.24.

[0007] This material introduces Ca into the bismuth potassium titanate matrix material. 0.5 Sr0.5 HfO3, using solid phase method to synthesize (1-x)Bi 0.5 K 0.5 TiO3-xCa 0.5 Sr 0.5 HfO3 solid solution, in the embodiments, the x value is 0.06, 0.12, 0.18, 0.24, and 0.30.

[0008] The present invention performs doping modification on bismuth potassium titanate-based ceramic materials, and the introduced Ca 0.5 Sr 0.5 Ca in HfO3 2 + and Sr 2+ Due to the difference in chemical valence and ion size between the A-site ions in the matrix crystal structure and Hf 4+ The difference in size from the B-site ion can enhance the polarization between ions. At the same time, due to the volatilization of potassium, an A-site ion vacancy is generated in the crystal structure, which greatly increases the (1-x)Bi 0.5 K 0.5 TiO3-xCa 0.5 Sr 0.5 The ionic disorder in the HfO3 crystal structure is conducive to transforming the ordered macroscopic ferroelectric domains into disordered nanodomain clusters, reducing the residual polarization and polarization hysteresis. In addition, the grain size of this component is small and the sample resistance is large, which together with the increase in ionic disorder increases the breakdown field strength, thereby improving the energy storage density and efficiency.

[0009] The preparation method of the potassium bismuth titanate-based relaxor ferroelectric ceramic material comprises the following steps:

[0010] (1) According to (1-x)Bi 0.5 K 0.5 TiO3-xCa 0.5 Sr 0.5 Weigh raw materials in a stoichiometric ratio of HfO3, including a Bi-containing compound, a K-containing compound, a Ti-containing compound, a Ca-containing compound, a Sr-containing compound and a Hf-containing compound, put the raw materials in a ball mill, add alcohol to perform ball milling, and then sequentially dry and grind to obtain a powder;

[0011] (2) pre-calcining the powder obtained in step (1);

[0012] (3) adding a binder to the powder pre-sintered in step (2), grinding and granulating the powder, pressing the powder into a sheet, and then placing the sheet in a muffle furnace for debinding and sintering in sequence to obtain the potassium bismuth titanate-based relaxor ferroelectric ceramic material.

[0013] Preferably, in step (1), the Bi-containing compound is Bi2O3, the K-containing compound is one or both of K2CO3 and KHCO3; the Ti-containing compound is TiO2; the Ca-containing compound is CaCO3; the Sr-containing compound is one or both of SrCO3 and SrO; and the Hf-containing compound is HfO2.

[0014] Preferably, in step (1), the ball milling time is 3-7 h and the rotation speed is 200-500 r / min, so as to fully mix the raw materials.

[0015] Preferably, in step (2), the pre-sintering temperature is 600-1000° C. and the time is 1-4 h, so as to obtain a precursor powder for synthetic ceramics.

[0016] Preferably, in step (3), the binder is a PVA aqueous solution with a mass concentration of 2%-10%, and the mass ratio of the binder to the powder is 0.02:1 to 0.1:1; the tableting pressure is 3-9 MPa, the debinding temperature is 300-800 °C, and the debinding time is 2-4 h; the sintering temperature is 1000-1300 °C, and the sintering time is 1-3 h.

[0017] The beneficial effects brought about by the technical solution provided by the present invention include at least:

[0018] The preparation method can obtain potassium bismuth titanate-based relaxor ferroelectric ceramics with high energy storage density, high energy storage efficiency and excellent environmental stability. When x=0.24, the ceramic material is 0.76Bi 0.5 K 0.5 TiO3 - 0.24Ca 0.5 Sr 0.5 HfO3, with a breakdown field strength of 670 kV / cm, is higher than most bismuth potassium titanate-based energy storage ceramics. Its energy storage density is 14.4 J / cm 3 , with an energy storage efficiency of 88.0%. In addition, the ceramic also exhibits excellent environmental stability, with an energy storage density of 6.42 ± 0.2 J / cm at 30-160 °C. 3 ; Under 1-100 Hz test conditions, the energy storage density is 6.67 ± 0.08 J / cm 3 ; in 10 1 -10 8 The energy storage density is 6.70 ± 0.09 J / cm 3 Under these three test conditions, the energy storage efficiency is about 88.0%. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the following briefly introduces the drawings required for use in the description of the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.

[0020] Figure 1 The XRD pattern of potassium bismuth titanate-based relaxor ferroelectric ceramics prepared in Examples 1-5;

[0021] Figure 2 Bipolar PE diagram of potassium bismuth titanate-based relaxor ferroelectric ceramic samples prepared in Examples 1-5;

[0022] Figure 3 This is a SEM image of the potassium bismuth titanate-based relaxor ferroelectric ceramic prepared in Example 4;

[0023] Figure 4 The unipolar PE curves of the potassium bismuth titanate-based relaxor ferroelectric ceramics prepared in Example 4 under different electric field intensities;

[0024] Figure 5 The energy storage density and energy storage efficiency corresponding to the unipolar PE curve of the potassium bismuth titanate-based relaxor ferroelectric ceramic prepared in Example 4 at different electric field strengths;

[0025] Figure 6 The unipolar PE curve of the potassium bismuth titanate-based relaxor ferroelectric ceramic prepared in Example 4 at a temperature gradient of 40-160°C;

[0026] Figure 7 1 is the unipolar PE curve of the potassium bismuth titanate-based relaxor ferroelectric ceramic prepared in Example 4 at a test frequency of 1-100 Hz;

[0027] Figure 8 The bismuth potassium titanate-based relaxor ferroelectric ceramic prepared in Example 4 was heated to 10 1 -10 8 Unipolar PE curves under cycle number. DETAILED DESCRIPTION

[0028] In order to make the technical problems, technical solutions and advantages to be solved by the present invention more clear, a detailed description will be given below with reference to the accompanying drawings and specific embodiments.

[0029] Example 1

[0030] Preparation of 0.94Bi 0.5 K 0.5 TiO3-0.06Ca 0.5 Sr 0.5HfO3 relaxor ferroelectric ceramics, including the following steps: weigh 5.4750 grams of Bi2O3, 1.6239 grams of K2CO3, 3.7537 grams of TiO2, 0.1501 grams of CaCO3, 0.2214 grams of SrCO3, and 0.6314 grams of HfO2 according to the chemical dosage ratio, and the weighing error is between 0 and + 0.0005 grams. Pour the weighed raw materials into a ball mill, add anhydrous ethanol and ball mill for 6 hours at a speed of 300 r / min, and dry and grind the ball-milled samples in turn. Then place the evenly mixed powder in a crucible, cover it, put it into a muffle furnace, set the temperature to 820 ° C and calcine for 2 hours. After cooling, take the sample and place it in a mortar, add 0.4 ml of PVA binder and grind it into granules, grind it evenly, and pour it into = 10 mm mold by a cold isostatic press at a pressure of 6 MPa to form a sheet, then the sheet is placed in a muffle furnace for debinding at 550 °C for 2 h, and then sintered at 1120 °C for 2 h to obtain a potassium bismuth titanate-based relaxor ferroelectric ceramic material.

[0031] Example 2

[0032] Preparation of 0.88Bi 0.5 K 0.5 TiO3-0.12Ca 0.5 Sr 0.5 HfO3 relaxor ferroelectric ceramics, including the following steps: weigh 5.1255 grams of Bi2O3, 1.5202 grams of K2CO3, 3.5141 grams of TiO2, 0.3002 grams of CaCO3, 0.4428 grams of SrCO3, and 1.2629 grams of HfO2 according to the chemical dosage ratio, and the weighing error is between 0 and + 0.0005 grams. Pour the weighed raw materials into a ball mill, add anhydrous ethanol and ball mill for 6 hours at a speed of 300 r / min, and dry and grind the ball-milled samples in turn. Then place the evenly mixed powder in a crucible, cover it, put it into a muffle furnace, set the temperature to 820 ° C and calcine for 2 hours. After cooling, take the sample and place it in a mortar, add 0.4 ml of PVA binder and grind it into granules, grind it evenly, and pour it into = 10 mm mold by a cold isostatic press at a pressure of 6 MPa to form a sheet, then the sheet is placed in a muffle furnace for debinding at 550 °C for 2 h, and then sintered at 1120 °C for 2 h to obtain a potassium bismuth titanate-based relaxor ferroelectric ceramic material.

[0033] Example 3

[0034] Preparation of 0.82Bi 0.5 K 0.5 TiO3-0.18Ca 0.5 Sr 0.5HfO3 relaxor ferroelectric ceramics, including the following steps: weigh 4.7760 grams of Bi2O3, 1.416 grams of K2CO3, 3.2745 grams of TiO2, 0.4504 grams of CaCO3, 0.6643 grams of SrCO3, and 1.8944 grams of HfO2 according to the chemical dosage ratio, and the weighing error is between 0 and + 0.0005 grams. Pour the weighed raw materials into a ball mill, add anhydrous ethanol and ball mill for 6 hours at a speed of 300 r / min, and dry and grind the ball-milled samples in turn. Then place the evenly mixed powder in a crucible, cover it, put it into a muffle furnace and set the temperature to 820 ° C to calcine for 2 hours. After cooling, take the sample and place it in a mortar, add 0.4 ml of PVA binder and grind it into granules, grind it evenly, and pour it into = 10 mm mold and pressed into sheets at a pressure of 6 MPa using a cold isostatic press. The sheets were then placed in a muffle furnace and debinded at 550 °C for 2 h and sintered at 1120 °C for 2 h to obtain a potassium bismuth titanate-based relaxor ferroelectric ceramic material.

[0035] Example 4

[0036] Preparation of 0.76Bi 0.5 K 0.5 TiO3-0.24Ca 0.5 Sr 0.5 HfO3 relaxor ferroelectric ceramics, including the following steps: weigh 4.4266 grams of Bi2O3, 1.3129 grams of K2CO3, 3.0349 grams of TiO2, 0.6005 grams of CaCO3, 0.8857 grams of SrCO3, and 2.5258 grams of HfO2 according to the chemical dosage ratio, and the weighing error is between 0 and + 0.0005 grams. Pour the weighed raw materials into a ball mill, add anhydrous ethanol and ball mill for 6 hours at a speed of 300 r / min, and dry and grind the ball-milled samples in turn. Then place the evenly mixed powder in a crucible, cover it, put it into a muffle furnace and set the temperature to 820 ° C to calcine for 2 hours. After cooling, take the sample and place it in a mortar, add 0.4 ml of PVA binder and grind it into granules, grind it evenly, and pour it into = 10 mm mold using a cold isostatic press at 6 MPa pressure to form a sheet, then put the sheet into a muffle furnace at 550 ° C for 2 h to remove binder, and then sintered at 1120 ° C for 2 h to obtain a bismuth potassium titanate-based relaxor ferroelectric ceramic material with high energy storage density, high energy storage efficiency and excellent environmental stability. After cooling, the ceramic sheet was polished to a thickness of 40-50 μm, and gold-plated electrodes were sprayed on its upper and lower surfaces for energy storage performance testing.

[0037] Example 5

[0038] Preparation of 0.70Bi 0.5 K 0.5TiO3-0.30Ca 0.5 Sr 0.5 HfO3 relaxor ferroelectric ceramics, including the following steps: weigh 4.0771 grams of Bi2O3, 1.2092 grams of K2CO3, 2.7953 grams of TiO2, 0.7507 grams of CaCO3, 1.1072 grams of SrCO3, and 3.1573 grams of HfO2 according to the chemical dosage ratio, and the weighing error is between 0 and + 0.0005 grams. Pour the weighed raw materials into a ball mill, add anhydrous ethanol and ball mill for 6 hours at a speed of 300 r / min, and dry and grind the ball-milled samples in turn. Then place the evenly mixed powder in a crucible, cover it, put it into a muffle furnace and set the temperature to 820 ° C to calcine for 2 hours. After cooling, take the sample and place it in a mortar, add 0.4 ml of PVA binder and grind it into granules, grind it evenly, and pour it into = 10 mm mold using a cold isostatic press at 6 MPa pressure to form a sheet, then put the sheet into a muffle furnace at 550 ° C for 2 h to remove binder, and then sintered at 1120 ° C for 2 h to obtain a bismuth potassium titanate-based relaxor ferroelectric ceramic material with high energy storage density, high energy storage efficiency and excellent environmental stability. After cooling, the ceramic sheet was polished to a thickness of 40-50 μm, and gold-plated electrodes were sprayed on its upper and lower surfaces for energy storage performance testing.

[0039] Figure 1 The powder XRD diagram of the bismuth potassium titanate-based relaxor ferroelectric ceramics prepared in Examples 1 to 5. As can be seen from the figure, the bismuth potassium titanate-based relaxor ferroelectric ceramic samples of Examples 1 to 5 all have a single cubic perovskite structure, and no obvious impurity phase is observed.

[0040] Figure 2 The bipolar PE diagram of the bismuth potassium titanate-based relaxor ferroelectric ceramic samples prepared in Examples 1-5. The applicant found that when x=0, a pure phase cannot be synthesized. When Ca is added to the bismuth potassium titanate-based 0.5 Sr 0.5 HfO3 can synthesize a stable perovskite phase. 0.5 Sr 0.5 The molar content of HfO3 gradually increases from 6 mol.% (x=0.06, Example 1) to 30 mol.% (x=0.30, Example 5), Figure 2 It can be seen that the hysteresis loop gradually becomes thinner, indicating that the polarization hysteresis is decreasing and the energy storage capacity is improved. Although the hysteresis of the ceramic prepared in Example 4 (x=0.24) is slightly larger than that of the ceramic prepared in Example 5 (x=0.30), its maximum polarization intensity is relatively larger and has the potential for high energy storage performance, so Example 4 is selected in the present invention for a more detailed energy storage performance test.

[0041] Figure 3This is a SEM image of the potassium bismuth titanate-based relaxor ferroelectric ceramic prepared in Example 4, which shows that the average grain size of the ceramic is about 0.4 μm, which is beneficial to improving the breakdown field strength of the sample.

[0042] Figure 4 The unipolar hysteresis loops of the 40-50 μm thick potassium bismuth titanate-based relaxor ferroelectric ceramic samples prepared in Example 4 under different electric fields show that the ceramic hysteresis loop is slender, the residual polarization and polarization hysteresis are small, and the maximum electric field strength can reach 670 kV / cm.

[0043] Figure 5 The energy storage density (W) corresponding to the unipolar hysteresis loop of the 40-50 μm thick potassium bismuth titanate-based relaxor ferroelectric ceramic sample prepared in Example 4 under different electric fields is rec ) and efficiency, the energy storage efficiency is 88.0% under the maximum electric field.

[0044] Figure 6 The unipolar hysteresis loop of the 40-50 μm thick potassium bismuth titanate-based relaxor ferroelectric ceramic sample prepared in Example 4 at a temperature gradient of 40-160 °C. The test electric field is 350 kV / cm. Under this test condition, its energy storage density is 6.42±0.2 J / cm 3 It can be seen that the energy storage density of the sample has good temperature stability.

[0045] Figure 7 The unipolar hysteresis loops of the 40-50 μm thick potassium bismuth titanate-based relaxor ferroelectric ceramic sample prepared in Example 4 at room temperature and 400 kV / cm electric field strength at different test frequencies, with the test frequency being 1-100 Hz. Under this test condition, its energy storage density is 6.67 ± 0.08 J / cm 3 , it can be seen that the energy storage density of the sample has good frequency stability.

[0046] Figure 8 The unipolar hysteresis loops of the 40-50 μm thick potassium bismuth titanate-based relaxor ferroelectric ceramic sample prepared in Example 4 at different cycle times at room temperature and an electric field strength of 400 kV / cm. The cycle number is 10 1 -10 8 Under this test condition, its energy storage density is 6.70 ± 0.09 J / cm 3 It can be seen that the energy storage density of the sample has good cycle stability.

[0047] The above is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any person skilled in the art can easily think of changes or substitutions within the technical scope disclosed by the present invention, which should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.

Claims

1. A high energy storage potassium bismuth titanate-based relaxor ferroelectric ceramic material with excellent environmental stability, It is characterized in that The chemical formula of the material is: (1-x)Bi 0.5 K 0.5 TiO 3 -xCa 0.5 Sr 0.5 HkDJ 3 , where x is Ca 0.5 Sr 0.5 HkDJ 3 The doping coefficient is x=0.06-0.

30.

2. The method for preparing the potassium bismuth titanate-based relaxor ferroelectric ceramic material according to claim 1, It is characterized in that The following steps are involved: (1) According to (1-x)Bi 0.5 K 0.5 TiO 3 -xCa 0.5 Sr 0.5 HkDJ 3 Weighing raw materials in a stoichiometric ratio, including a Bi-containing compound, a K-containing compound, a Ti-containing compound, a Ca-containing compound, a Sr-containing compound and a Hf-containing compound, placing the raw materials in a ball mill, adding alcohol for ball milling, and then drying and grinding in sequence to obtain a powder; (2) pre-calcining the powder obtained in step (1); (3) adding a binder to the powder pre-sintered in step (2), grinding and granulating the powder, pressing the powder into tablets, and then placing the tablets in a muffle furnace for debinding and sintering in sequence to obtain the potassium bismuth titanate-based relaxor ferroelectric ceramic material.

3. The preparation method according to claim 2, It is characterized in that In step (1), the Bi-containing compound is Bi 2 O 3 ; The K-containing compound is K 2 CO 3 , KHCO 3 One or two of the following; the Ti-containing compound is TiO 2 ; The Ca-containing compound is CaCO 3 ; The Sr-containing compound is SrCO 3 , SrO or both; the Hf-containing compound is HfO 2 .

4. The preparation method according to claim 2, It is characterized in that In step (1), the ball milling time is 3-7h and the rotation speed is 200-500r / min.

5. The preparation method according to claim 2, It is characterized in that In step (2), the pre-firing temperature is 600-1000° C. and the time is 1-4 hours.

6. The preparation method according to claim 2, It is characterized in that In step (3), the binder is a PVA aqueous solution with a mass concentration of 2%-10%, and the tableting pressure is 3-9MPa.

7. The preparation method according to claim 2, It is characterized in that In step (3), the debinding temperature is 300-800°C, the debinding time is 2-4h, the sintering temperature is 1000-1300°C, and the sintering time is 1-3h.